Bariery implementacji wirtualnego outsourcingu informatycznego - Dziembek, Damian (The Barriers of Virtual Outsourcing on Information Systems' Implementation, 2007)
The aim of this article is to identity and to present barriers of virtual outsourcing on information systems' implementation. The virtual outsourcing on information systems can be a new form of outsourcing IT realization. After introduction of virtual outsourcing on information systems, the different types of barriers were presented. The barriers which influence virtual outsourcing on information systems' implementation are divided into: financial barriers, security barriers, social and cultural barriers, and the organizational barriers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (11); 2007; nr 1156, s. 125-140